Therapy of multiple myeloma - Goldschmidt, Hartmut; Cremer, Friedrich Walter; Möhler, Thomas; Krämer, Alwin; Görner, Martin; Egerer, Gerlinde; Ho, Anthony Dick (The Chinese-german journal of clinical oncology, 2002)
Multiple Myeloma (MM) is characterised by the accumulation of malignant plasma cells in the bone marrow producing a monoclonal immunoglobulin. The standard conventional therapy is the combination of melphalan and prednisone resulting in a response rate of 40%-60% and in a median survival time of approximately 3 years. In order to improve the therapeutic efficacy various combination regimens have been tested. Most randomized trials have frailed to show a significant improvement in survival time when combination chemotherapy is used instead of melphalan with or without prednisone. The benefit of maintenance therapy with interferon-alpha has been demonstrated. The toxicity of interferon-alpha, which may reduce the quality of life, should be considered. Recently, myeloma-treatment has been modified. High-dose chemotherapy accompanied by hematopoietic stem-cell support via autologous transplant is recommended up to the age of 65-70 years. First results from a French study comparing single versus double autologous transplantation have shown a benefit in terms of event-free survival for the sequential approach. Vaccinations as an adoptive immuntherapy to treat minimal residual disease are under way. The mortality rate of allogeneic transplantation of hematopoietic stem cells has been reduced in the last 5 years. The use of reduced conditioning regimens or the partial depletion of T cells in peripheral blood stem cell transplants in an effort to decrease transplant related mortality are promising approaches. Thalidomide and its derivates are a new class of agents with independent anti-tumour activity in MM. Encouraging results with this antiangiogenic therapy in phase II trials have been reported. Supportive therapies, such as the treatment of anaemia with erythropoietin, the management of renal failure and the use of bisphosphonates, improve the life quality of MM patients.
Gesehen am 11.02.2022